2023
DOI: 10.1186/s13044-023-00166-4
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the care of patients with RET-altered thyroid cancer: a multicountry mixed-methods study

Suzanne Murray,
Vivek Subbiah,
Steven I. Sherman
et al.

Abstract: Background The discovery of driver oncogenes for thyroid carcinomas and the identification of genomically targeted therapies to inhibit those oncogenes have altered the treatment algorithm in thyroid cancer (TC), while germline testing for RET mutations has become indicated for patients with a family history of RET gene mutations or hereditary medullary TC (MTC). In the context of an increasing number of selective RET inhibitors approved for use, this paper aims to describe challenges and barri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…That said, even within the survey, testing RET fusions in MTC has been reported by practitioners regularly prescribing molecular genotyping; this might reflect lack of awareness considering that RET fusions in MTC exist in literature only as case reports [ 32 ]. In support, a recent international study among pathologists from Germany, the UK, Japan and the USA reported considerable knowledge and skill gaps in RET testing for lung cancer and TC [ 33 , 34 ]. It is also worth mentioning that half of the surveyed practitioners could not consult an institutional tumour board.…”
Section: Discussionmentioning
confidence: 99%
“…That said, even within the survey, testing RET fusions in MTC has been reported by practitioners regularly prescribing molecular genotyping; this might reflect lack of awareness considering that RET fusions in MTC exist in literature only as case reports [ 32 ]. In support, a recent international study among pathologists from Germany, the UK, Japan and the USA reported considerable knowledge and skill gaps in RET testing for lung cancer and TC [ 33 , 34 ]. It is also worth mentioning that half of the surveyed practitioners could not consult an institutional tumour board.…”
Section: Discussionmentioning
confidence: 99%